Comparative immunohistochemical analysis of inflammatory cytokines in distinct subtypes of Sweet syndrome - Chieosilapatham, Panjit; Daroontum, Teerada; Suwansirikul, Songkiet; Chaiwarith, Romanee; Phinyo, Phichayut; Chaowattanapanit, Suteeraporn; Choonhakarn, Charoen; Kiratikanon, Salin; Rujiwetpongstorn, Rujira; Tovanabutra, Napatra; Chiewchanvit, Siri; Chuamanochan, Mati (Frontiers in Immunology, 2024)
A dysregulated immune response has been implicated in Sweet syndrome (SS) pathogenesis; however, cytokine profiles across different conditions associated with SSincluding adult-onset immunodeficiency (AOID) due to anti-interferon (IFN)-γ autoantibodiesremain unknown. The purpose of the study is to investigate alterations in inflammatory cytokines in skin lesions of distinct subtypes of SS. Skin biopsies were collected from 42 AOID-and 52 non-AOID-associated SS patients and 18 healthy controls. The comparative immunohistochemical study was conducted using monoclonal antibodies against interleukin (IL)-1β, IL-6, IL-17, IFN-γ, and tumor necrosis factor-α on paraffin-embedded sections. The quantitative percentage positivity and intensity were calculated using computer-based image analysis. The results showed stronger and more diffuse dermal immunoreactivity for IFN-γ and IL-17 in the AOID-associated (p < 0.001 and p < 0.001, respectively) and non-AOID-associated SS (p < 0.001 and p < 0.001, respectively) groups. However, no significant differences in the levels of these two cytokines were observed between AOID-and non-AOID-associated SS groups. Increased expression of IFN-γ together with IL-17 was also noted in almost all subtypes among non-AOID-associated SS. Together, these results demonstrate that IFN-γ and IL-17 are implicated in immunopathology of all SS subtypes, including AOID-associated SS, despite the presence of anti-IFN-γ autoantibodies.